2017
DOI: 10.1017/aaq.2017.46
|View full text |Cite
|
Sign up to set email alerts
|

The Ideal Distribution of Farmers: Explaining the Euro-American Settlement of Utah

Abstract: Explaining how and why populations settle a new landscape is central to many questions in American archaeology. Recent advances in settlement research have adopted predictions from the Ideal Free Distribution model (IFD). Explicar cómo y por qué las poblaciones se instalan en un nuevo lugar es fundamental para muchas preguntas en la arqueología americana. Los avances recientes en la investigación de asentamientos han adoptado las predicciones del modelo de Distribución Libre Ideal (DLI). Mientras que las prueb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…While we do not account for past climate change, we assume that any past climate variations were homogeneous across the GSENM. That is if climate became hotter and dryer by an order of magnitude in one area, it also became hotter and dryer by a similar magnitude in other areas, with the relative difference remaining constant [71].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…While we do not account for past climate change, we assume that any past climate variations were homogeneous across the GSENM. That is if climate became hotter and dryer by an order of magnitude in one area, it also became hotter and dryer by a similar magnitude in other areas, with the relative difference remaining constant [71].…”
Section: Plos Onementioning
confidence: 99%
“…Assuming that individuals seek to maximize their rate of energetic return (see [63,69]), they should prefer to occupy locations of higher environmental productivity [26]. While most often applied to hunting and gathering populations [70], this logic also holds for agriculturalists [71]. Given that the broad diets of agriculturalists [72] consisted of less profitable resources requiring significant investment in handling rather than search, they should be less mobile and, therefore, more sensitive to variation in environmental productivity [73].…”
Section: Environmental Predictor Variablesmentioning
confidence: 99%
“…Miller and Carmody (this issue) follow up on this work by showing that settlement dynamics shift from being largely 'free' in the early Holocene, to more Allee-like in the middle Holocene, and finally more despotic in the late Holocene. Yaworsky and Codding (2018) showed that IDMs need not only be applied in prehistoric contexts by demonstrating that the Euro-American colonisation of Utah in the nineteenth and twentieth centuries conformed to predictions of the IFD, with settlers preferring areas with high moisture and agricultural potential. Given the common occurrence of human colonisation events and migrations throughout history, much opportunity exists to apply IDMs and future work could benefit from attention to population movements into already-occupied landscapes as well as the interplay between prey and patch choice dynamics and demographic expansion.…”
Section: Colonisation and Migrationmentioning
confidence: 99%
“…IFD and IDD models have been adapted to diverse scales, including small islands (Winterhalder et al, 2010), a state such as California (Yaworsky & Codding, 2018), In the present analysis, we have violated some assumptions of the basic model in applying the IFD to the case of historical China.…”
Section: Ideal Free and Despotic Modelsmentioning
confidence: 99%
“…IFD and IDD models have been adapted to diverse scales, including small islands (Winterhalder et al, 2010), a state such as California (Yaworsky & Codding, 2018), and occupation of the Pacific and its subregions (O'Connell & Allen, 2012). These examples cover huntergatherer, pastoralist, and agricultural production systems.…”
Section: Ideal Free and Despotic Modelsmentioning
confidence: 99%